Multi-hop wireless network oriented multiple jammers localization algorithm - Qi-ping WANG; Xiang-lin WEI; Jian-hua FAN; Tong-xiang WANG; Fei HU (Tongxin xuebao)
A multiple jammer localization algorithm in multi-hop wireless networks was proposed. The proposed algo-rithm contained three steps, packet delivery ratio (PDR) valley point determination based on gradient descent algorithm, received jamming signal strength (RJSS) peak point determination based on gradient ascent algorithm and cluster analysis. Firstly, the algorithm started from a few initial nodes and moved along the gradient descent direction of PDR to approach the jammers until reaches the PDR valley point. Then, the algorithm moved toward the jammers using power adaptation technique based on RJSS gradient ascent process until it reached the RJSS peak point. Finally, through applying cluster analysis on the neighbour nodes which fail to communicate with RJSS peak points, the number and positions of the jam-mers can be estimated. Experimental results have verified that the proposed algorithm can improve the accuracy of local-ization compared with existed localization algorithms. Furthermore, the performance of the proposed algorithm is promi-nent when the distance of jammers accords with constraint condition.